Deutsche Zeitschrift für Philosophie : Zweimonatsschrift der internationalen philosophischen Forschung (De Gruyter (A), 1953)
As an open forum for discussion, Deutsche Zeitschrift für Philosophie promotes dialog between different philosophical cultures, transcending any one school of thought. The journal primarily publishes studies that are actively engaged in modern international philosophical discourse and explore new conceptual approaches. In addition to scholarly papers, essays, interviews, and symposia, the journal presents discussions and book reviews.